PENGARUH AWARENESS OF CONSEQUENCES, PERIKLANAN DAN SELF IDENTITY TERHADAP STRATEGI DIGITAL MARKETING PADA UMKM KERAJINAN DI KOTA KEDIRI - Komari, Ana (Universitas Putera Batam, 2025)
This study aims to determine the influence of factors such as awareness of concequence, advertising, self-identity, and digital marketing strategies in improving marketing decisions in Handicraft MSMEs in the city of Kediri and provide benefits in terms of functionality and policies of the Mayor of Kediri in prioritizing these factors. A quantitative method with multiple linear regression analysis was used to collect primary data with a direct survey of all MSME owners in the handicraft product category in the city of Kediri. The results of the analysis show that the Awareness Consequence strategy should adopt an ethical approach in doing business, expand the reach of the local base, and focus on customer satisfaction. The Advertising Strategy must choose the optimal platform, understand the needs of the customer, and implement the right design, advertise with a relevant local base, and understand the needs of the customer. Meanwhile, the Self Identity strategy must make ethical marketing decisions, increase environmental awareness, and give an identity to the brand by understanding what the needs of users are. This can help increase the sales of handicraft MSMEs in the city of Kediri and have an economic impact on the local area.